2014
DOI: 10.1186/1471-2350-15-7
|View full text |Cite
|
Sign up to set email alerts
|

The novel p.Cys65Tyr mutation in NR5A1gene in three 46,XY siblings with normal testosterone levels and their mother with primary ovarian insufficiency

Abstract: BackgroundDisorders of sex development (DSD) is the term used for congenital conditions in which development of chromosomal, gonadal, or phenotypic sex is atypical. Nuclear receptor subfamily 5, group A, member 1 gene (NR5A1) encodes steroidogenic factor 1 (SF1), a transcription factor that is involved in gonadal development and regulates adrenal steroidogenesis. Mutations in the NR5A1 gene may lead to different 46,XX or 46,XY DSD phenotypes with or without adrenal failure. We report a Brazilian family with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 36 publications
4
29
0
3
Order By: Relevance
“…The identification of a mutation in the specific gene is important for the follow-up of these cases, particularly mutations in WT1 that are associated with risk of kidney cancer and gonadal and renal failure [30, 31]. NR5A1 mutations are associated with risk of adrenal insufficiency and primary ovarian failure [3234]. In a family with mutation in SRY , there was a wide spectrum of XY gonadal dysgenesis manifestation, varying from partial to complete forms [28].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of a mutation in the specific gene is important for the follow-up of these cases, particularly mutations in WT1 that are associated with risk of kidney cancer and gonadal and renal failure [30, 31]. NR5A1 mutations are associated with risk of adrenal insufficiency and primary ovarian failure [3234]. In a family with mutation in SRY , there was a wide spectrum of XY gonadal dysgenesis manifestation, varying from partial to complete forms [28].…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal function was normal for all siblings. The mutation c.195G > A (p.Cys65Tyr) was identified within exon 3 in the three siblings and also in the mother (Fabbri et al., ).…”
Section: Methodsmentioning
confidence: 98%
“…Patients with normal testosterone production and spontaneous puberty have been described before [Bashamboo et al, 2010;Fabbri et al, 2014], but some presented with progressive gonadal dysgenesis resulting in oligospermia or azoospermia, as in patient 2 [Tantawy et al, 2012]. Pedace et al [2014] suggested that NR5A1 alterations may affect Sertoli cells more severely than Leydig cells, considering that most of the 46,XY patients will produce testosterone during life, maintaining the function of Leydig cells in adulthood, although it might be lower than that of normal cells.…”
Section: Discussionmentioning
confidence: 99%